Plant Genes Benefitting Aphids—Potential for Exploitation in Resistance Breeding - Åhman, Inger; Kim, Sung-Yong; Zhu, Li-Hua (Frontiers in Plant Science, 2019)
Aphids are phloem sap-feeding insects common as pests in various crops. Here we review 62 omics studies of aphid/plant interactions to search for indications of how aphids may manipulate the plants to make them more suitable as hosts, i.e. more susceptible. Our aim is to try to reveal host plant susceptibility (S) genes, knowledge which can be exploited for making a plant more resistant to its pest by using new plant breeding techniques to knock out or down such S genes. S genes may be of two types, those that are involved in reducing functional plant defense and those involved in further increasing plant factors that are positive to the aphid, such as facilitated access to food or improved nutritional quality. Approximately 40% of the omics studies we have reviewed indicate how aphids may modify their host to their advantage. To exploit knowledge obtained so far, we suggest knocking out/down candidate aphid S genes using CRISPR/Cas9 or RNAi techniques in crops to evaluate if this will be sufficient to keep the aphid pest at economically viable levels without severe pleiotropic effects. As a complement, we also propose functional studies of recessively inherited resistance previously discovered in some aphid–crop combinations, to potentially identify new types of S genes that later could be knocked out or down also in other crops to improve their resistance to aphids.